PENGEMBANGAN MODUL PEMBELAJARAN SEJARAH KONTROVERSIAL BERBASIS PROBLEM SOLVING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA SMA - Listyaputri, Dinar Rizky; Sariyatun, S.; Agung S., Leo (HISTORIKA, 2018)
The aims of this research were: (1) to describe the process of history learning in high school in Surakarta; (2) to develop learning material which is a module of controversial history with problem solving as learning method, and (3) to analyze effectiveness of module to improve student’s critical thinking skill. The method of this research was R&D and used ADDIE as the model. Methods of data collection were interviewing, document analysis, and critical thinking test. Data analysis was done by non parametric-statistical analysis. Results of this research showed: (1) both teacher and students still learned history by using conventional method and never been studying controversial history; (2) controversial history module got scored by validator with the score average up to 146/153 or 95%; (3) analysis result of score of students critical thinking showed the differences point between control and experiment class was 0,007 and the effectiveness score of module reached 0,01 which meant the module was effective enough to be applied to increase students critical thinking.